TINJAUAN HUKUM ISLAM TERHADAP HAK PEREMPUAN DALAM MEMILIH PASANGAN HIDUP: Studi Kasus di Desa Dolago Padang Kecamatan Parigi Selatan Kabupaten Parigi Moutong - Rahmadani; Jumat, Gani; Mursyid, Besse Tenriabeng (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2023)
Islam provides women with rights under the Prophet Muhammad SAW. With the changes, women have full freedom of ownership rights in all permitted ways and have full rights to express opinions when they are asked to express their opinions. This research uses sociological research methods on law using empirical data collected through techniques. observation, interviews and documentation, the data analysis techniques used are data reduction, data presentation and checking the validity of the data. From women's opinions regarding the implementation of women's rights in choosing a life partner, not all implementations of women's rights have been implemented because they are still held by those closest to them. Therefore, the importance of communication and education in determining life choices. As the Hanafi school of thought emphasizes that women have the right to choose. The Prophet also said "marry someone you like". However, the facts on the ground contradict the existing theory. The supporting factors for reviewing Islamic law towards women are socio-economic background, education, mature age and parents. Inhibiting factors are the will or choice of parents, lack of readiness of men chosen by women, men who are economically disadvantaged, women who are still in the process, social and family factors and others.